ULCER DISEASE - Atoeva Munishon Nabievna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: Peptic ulcer disease (PU) develops with continued activity of the internal gastrointestinal tract (GIT) due to the secretion of gastric acid or pepsin. Epigastric pain usually occurs 15–30 minutes after eating in patients with gastric ulcers; on the other hand, pain from a duodenal ulcer usually occurs 2-3 hours after eating. PU is a global problem, the risk of development of which ranges from 5% to 10 %. Overall, there has been a decline in the incidence of ulcers worldwide due to improved hygiene and sanitation in the UK with effective treatment and judicious use of NSAIDs. Duodenal ulcers are four times more common than stomach ulcers. Also, duodenal ulcers are more common in men than in women.